Stripe instabilities in the menisci of free-standing smectic films: influence of the phase sequence of the mesogenic material. Issue 10 (9th August 2018) - Loudet, J.-C.; Selmi, M.; Dolganov, P. V.; Othman, T.; Cluzeau, P.
ABSTRACT: We briefly report experimental observations of striped patterns in the menisci of free-standing smectic C films. The results were obtained with a mesogenic compound that transits directly from the nematic phase to the smectic C phase, without an intermediate smectic A phase. In this case, it is shown that stripes do not correspond to undulations of the smectic free surface and smectic layers, as was indeed evidenced in previous studies with other compounds and different phase sequences. Hence, our results show that the nature of striped patterns in free-standing films depends on the phase sequence of the considered materials. Further experimental and theoretical works are still required to fully elucidate the physical mechanisms that drive the onset of patterns in such systems. GRAPHICAL ABSTRACT: